Stability and equation of state of face-centered cubic and hexagonal close packed phases of argon under pressure - Agnès Dewaele (Nature Portfolio, 2021)
Abstract The compression of argon is measured between 10 K and 296 K up to 20 GPa and and up to 114 GPa at 296 K in diamond anvil cells. Three samples conditioning are used: (1) single crystal sample directly compressed between the anvils, (2) powder sample directly compressed between the anvils, (3) single crystal sample compressed in a pressure medium. A partial transformation of the face-centered cubic (fcc) phase to a hexagonal close-packed (hcp) structure is observed above 4.2–13 GPa. Hcp phase forms through stacking faults in fcc-Ar and its amount depends on pressurizing conditions and starting fcc-Ar microstructure. The quasi-hydrostatic equation of state of the fcc phase is well described by a quasi-harmonic Mie–Grüneisen–Debye formalism, with the following 0 K parameters for Rydberg-Vinet equation: $$V_0$$ V 0 = 38.0 Å $$^3$$ 3 /at, $$K_0$$ K 0 = 2.65 GPa, $$K'_0$$ K 0 ′ = 7.423. Under the current experimental conditions, non-hydrostaticity affects measured P–V points mostly at moderate pressure ( $$\le$$ ≤ 20 GPa).